Ascorbic Acid Contents in Chili Peppers (Capsicum L.) - Owk ANIEL KUMAR; Sape SUBBA TATA (Notulae Scientia Biologicae, 2009)
The genus Capsicum commonly known as chili pepper is a major spice crop and is almost cosmopolitan in distribution. The nutritive value of chili pepper is largely determined by ascorbic acid content. The fruits at five ripening stages viz., (M1, M2, M3, M4 and M5) from seventeen cultivars of Capsicum annuum L and one cultivar of Capsicum frutescens L were analyzed for ascorbic acid content. Among eighteen genotypes the C. annuum var. IC: 119262(CA2) showed higher ascorbic acid content (mg/100g) FW i.e., 208.00.68 (M1), 231.00.66 (M2), 280.00.31 (M3), 253.00.34 (M4) and 173.70.27 (M5). The study revealed that the gradual increase in ascorbic acid content from green to red and subsequently declined in the lateral stages (red partially dried and red fully dried fruits). The variability of ascorbic acid content in the genotypes suggests that these selected genotypes may be use full as parents in hybridization programs to produce fruits with good nutritional values.